Professor Alessandro Zuddas’ impact and legacy: the influential networking and human connection akills of a passionate scientist, clinical academic, and pioneer in child and adolescent psychopharmacology - Carucci, Sara; Di Martino, Adriana; Castellanos, Francisco Xavier; Masi, Gabriele; Banaschewski, Tobias; Coghill, David; Moreno, Carmen; Cortese, Samuele (Journal of child and adolescent psychopharmacology, 2024)
Professor Alessandro Zuddas, from the University of Cagliari (Italy), passed away prematurely in July 2022. As a prominent figure in child and adolescent neuropsychiatry, he substantially influenced the fields of neurodevelopmental disorders and neuropsychopharmacology both nationally and internationally. Professor Zuddas was a renowned expert in basic and clinical research in child and adolescent psychopharmacology, an enlightened and stimulating educator, and a mentor to many students, residents, and senior colleagues. With his enthusiasm and unique ability to network, he contributed enormously to trace a path in the field that we continue to follow. His name will remain in the textbooks and articles he authored. Here, as colleagues and friends who had the honor to work with him, we provide our personal views of Alessandro’s impact and legacy, which go far beyond his publications.
Gesehen am 07.04.2025